Achievable rates of SVD‐based codebooks for zero‐forcing and Tomlinson‐Harashima precoding schemes with limited feedback MU‐MIMO system. (20th May 2016) - Kaleem, Zeeshan; Hui, Bing; Chang, KyungHi
Summary: In this manuscript, we developed a new SVD‐based codebook design criterion for linear zero‐forcing (ZF) precoding and Tomlinson‐Harashima (TH) precoding with limited feedback. In limited feedback systems where only quantized channel state information is available, precoding on transmitter causes sum‐rate degradation because of quantization errors. Thus, we propose more efficient codebooks that reduce the quantization error with lower feedback overheads. We also develop a closed‐form expression for sum‐rate of the proposed codebooks in case of TH and ZF precoding schemes in a multiuser MIMO system with limited feedback. The numerical consequences prove that TH precoding can achieve sum‐rate gain of 0.5–2.5 bps/Hz at 25 dB signal‐to‐noise ratio as compared with linear ZF precoding with 10 and 20 feedback bits per user, respectively. Moreover, the numerical results also prove that the performance of nonlinear TH precoding is better than linear ZF precoding for low signal‐to‐noise ratio value or for the large number of feedback bits. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this manuscript, we propose a new SVD‐based codebook design criterion for linear zero‐forcing precoding and nonlinear Tomlinson‐Harashima precoding with limited feedback. In limited feedback system where only quantized channel state information is available, zero‐forcing and Tomlinson‐Harashima precoding on the transmitter side causes sum‐rate degradation because of quantization errors. Thus, we propose more efficient codebooks that reduce the quantization error with lower feedback overheads and also derive a closed‐form expression for the achievable sum‐rate of the proposed codebooks.